COMMUNITY-BASED TOURISM AND DESTINATION COMPETITIVENESS: BRIDGING THE GAP - Bassols Gardella, Narcís; Bonilla, Jorge (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
This article explores and discusses community-based tourism (CBT) and proposes a model intended to be exemplary for CBT cases throughout most of the world’s emerging countries. Further, this paper aims at establishing a connection between competitiveness and local CBT development, calling therefore the proposed model C-CBT. The authors try to establish the motivations to develop this type of tourism, as well as the drawbacks, grouping them into the C-CBT model. This model is then used as a comparative tool and applied to two territories in Colombia which have suffered from conflict in the last decades and have subsequently developed CBT. As for the field work in the two locales, it is based on interviews and observation carried out in the context of tourism development projects in both areas. The outcome is a clearer understanding of the factors that favor CBT initiatives and connects these with competitiveness frameworks, with the added interest that the presented cases come from a severely conflict-burdened country.